2014
DOI: 10.1111/ans.12721
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of general practitioners with specialty interests for surgical procedures

Abstract: Background: General practitioners with specialty interests (GPwSIs) have been an emerging entity in the last decade or so and aim to improve patient's access to specialist level care in the primary care setting. This is achieved by them providing equivalent quality and outcomes to secondary consultant-led services, while not necessarily providing the same breadth of clinical care as them. In this systematic review, we attempt to address their efficacy for surgical procedures and specialties. Methods: PRISMA gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 9 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…antibiotics) and limiting patients entering secondary care . Examples of the effect of additional training can be seen with dedicated and specialized GPs in Australia and the U.K., where they have a greater role in skin cancer management . In addition, further structuring of AK management, including explicit criteria for referral (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…antibiotics) and limiting patients entering secondary care . Examples of the effect of additional training can be seen with dedicated and specialized GPs in Australia and the U.K., where they have a greater role in skin cancer management . In addition, further structuring of AK management, including explicit criteria for referral (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…19,37,40,48,49 Examples of the effect of additional training can be seen with dedicated and specialized GPs in Australia and the U.K., where they have a greater role in skin cancer management. [50][51][52] In addition, further structuring of AK management, including explicit criteria for referral (e.g. AK not responding to treatment, AK in immunosuppressed patients, AK with the potential of SCC), may provide a substantive potential to lower the burden in secondary care.…”
Section: Discussionmentioning
confidence: 99%
“…This general upskilling of GPs has achieved a comparable standard of excisions to those reported for several GPwSI services. [22][23][24] The advantage of our programme is that it provides a wider base of competent practitioners, more convenient access to care for patients, and avoids the costs of accrediting doctors.…”
Section: Comparison With Similar Initiativesmentioning
confidence: 99%
“…172 Earlier models of providing specialist care in the community include interventions that involve the transfer of services where primary care substitutes for secondary care [e.g. GPs with specialist interests (GPwSIs) 71,173,174 or the relocation of services from secondary care to primary care settings). [174][175][176][177][178] More recently, the ways in which specialist care is being implemented in primary care go beyond the 'drag and drop' approach of simply relocating a hospital outpatient clinic into a community setting; instead, methods that put education at the core alongside the redesign of the patient pathway and/or the role of the professional are becoming more established.…”
Section: Characteristics Of Community-based Care and Primary Care Accessmentioning
confidence: 99%
“…164,181 In general, studies reporting on the transfer of care from secondary to primary care have reported that the quality of care achieves an acceptable standard. 71,173,174 The safety of diagnostic services transfer is equivocal; a literature-mapping exercise 175 found evidence that the quality (including diagnostic accuracy and the appropriateness of test ordering) and safety of diagnostic service provision in the community is mixed.…”
Section: Population Healthmentioning
confidence: 99%